A multi-objective optimization of PV/ST-GSHP system based on office buildings. (October 2018) - Fu, Yu; Lin, Haiyang; Sun, Kailai; Sun, Qie; Wennersten, Ronald
Abstract: Solar thermal heaters (STs), photovoltaics (PVs) and ground source heat pumps (GSHPs) are widely used nowadays due to their advantages of environmental protection and energy saving. The combination of solar thermal, photovoltaic and GSHP can achieve an even better performance and such a system is referred to as PV/ST-GSHP in this study. The overall efficiency of the PV/ST-GSHP system is highly dependent on the capacity size which is large or small would affect the overall efficiency and the power of PVs and STs affects the efficiency as well. This paper established an optimization model for a PV/ST-GSHP system based on the environment, energy and economy criteria. The model focused on the optimal planning of PV and ST under the restriction of a limited size of area and of the practical loads of heat and cooling, for which the rated capacity of GSHP is included. Genetic algorithm is employed to solve the optimization problem. After optimization, the multi-objective value is 26.88%.